Impacto da integração da geração fotovoltaica no conteúdo harmônico das microrredes - Aires, Osmar Lucas Dias (2022)
In recent years, distributed generation has become of great importance and attracting new research in the Brazilian electricity sector. However, the insertion of distributed generation in an electrical system without proper analysis of possible impacts can lead to the emergence of undesirable phenomena for both the utility and the consumer, such as the rise, fall or interruption of voltage, protection problems and control causing instability in the system and low quality of electricity for the final consumer. Based on that, this dissertation work evaluates the impact of the integration of photovoltaic generation on the harmonic content of microgrids, using as a basis a modified 13-bus IEEE model. The location of a PV source in the microgrid, its number of units and its penetration level are used as parameters to verify the effects and contributions of harmonics in the system. Harmonic detection methods are also presented, discussed and used. Simulations are performed through the software MATLAB/SimulinkTM and the results generated are analyzed in their respective section.